Issues in Global Natural Gas : A Primer and Analysis - Okogu, Bright (IMF Working Papers; Working Paper, 2002)
This paper discusses the rising profile of natural gas in global energy, factors constraining its further development, the gas contracting process, and the absence of a global market, which is analyzed in the context of the economic rent in the gas price and the opaque nature of gas contracts. A proposal for rationalizing the trade to ease these constraints is offered. Gas pricing, and factors driving demand are also analyzed using evidence from the literature. FDI can help to monetize some of the 'stranded' gas reserves, but success would depend on an investor-friendly climate, including appropriate tariff regimes in the domestic markets.